IMPLEMENTASI KEBIJAKAN PERATURAN WALIKOTA SURAKARTA NOMOR 13 TAHUN 2019 TENTANG TATA KELOLA DATA KEMISKINAN DAERAH TAHUN 2020- 2021 (STUDI EMPIRIS DI KOTA SURAKARTA PROVINSI JAWA TENGAH) - Taufan Adi Redina Purnama (JI@P, 2022)
The purpose of carrying out the research which is expected to be achieved is toanalyze the implementation of Mayor Regulation Number 13 of 2019 concerningRegional Poverty Data Governance.The research method used in this research is qualitative research. The purpose ofthis qualitative research is to analyze the implementation of mayoral regulationnumber 13 of 2019. This research is in the process of using data collectiontechniques in the form of observations and interviews with objects that will beused as the basis of research to examine the phenomenon of the existence of nonpoorcitizens entering the poverty database and the phenomenon of peopleclaiming to be poor to get assistance, therefore the researcher uses this type ofqualitative research.The results of the research conducted are that the governance of regional povertydata in accordance with Mayor Regulation No. 13 of 2019 has been carried outeffectively according to the plan of the Surakarta City Government. through thedata that has been presented based on Edward III's theory seen from 4 indicators:1. Communication: in the implementation of the policy, it has been carried outwell and clearly for all members of poverty data management, most of thecommunication is done with the whatups group so that problems can be quicklyresolved related to technical and policy issues. 2. Resource: In its implementation,there is already a division of tasks and responsibilities for each task and functionof the poverty data management team as well as utilizing technology in managingregional poverty data. 3.Disposition: governance of poverty data and has beenregulated in Mayor Regulation No. 4 of 2018. 4.Bureaucratic structure : theexistence of Standard Operating Procedure and main functions in carrying outthe duties and responsibilities of the team. So that the realization and planachievements prove that the activities of the poverty data management team arecarried out according to their duties and functions and achieve the predeterminedtargets. However, there is something that is less trusted, namely related to : 1.Communication: Communication that must be strengthened by the strategy ofdelivering information or outreach to the public about checking the status ofpoverty data through conventional methods or with social media, with this methodthe public will know the status in the poverty database. 2.Bureaucratic structure :Bureaucratic structure in the absence of Standard Operating Procedure thatregulate the movement of the poor so that it is confusing in data collection, whichresults in aid not being targeted.Keywords: communication, resources, disposition, organisation structures